2020
DOI: 10.3389/fcell.2020.00723
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Macrophage Function by Lactobacillus-Conditioned Medium

Abstract: Probiotics are used as microbial food supplements for health and well-being. They are thought to have immunomodulatory effects although their exact physiological mechanism of action is not clear. This study investigated the influence of probiotic Lactobacillus rhamnosus GG conditioned media (LGG-CM) on macrophage phagocytosis of non-pathogenic Escherichia coli HfrC. The gentamicin protection assay was used to study the bacterial killing phases of phagocytosis. Macrophages coincubated with E. coli for an hour a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…***p < 0.001. phagocytic bacterial clearance. In support of this, and using a conditioned medium obtained from cultures of L. rhamnsosus, Nanjundaiah et al [119] showed a dose-dependent increase in the bacterial killing ability of macrophages against E. coli, and that this was found to be associated with the enhanced production of reactive oxygen species (ROS) and nitric oxide (NO) in differential amounts, within macrophages. Similarly, Rocha-Ramirez et al [120] demonstrated that the pretreatment of macrophages with varying Lactobacillus strains increased their phagocytic and bactericidal activity toward pathogens including S. aureus and E. coli.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…***p < 0.001. phagocytic bacterial clearance. In support of this, and using a conditioned medium obtained from cultures of L. rhamnsosus, Nanjundaiah et al [119] showed a dose-dependent increase in the bacterial killing ability of macrophages against E. coli, and that this was found to be associated with the enhanced production of reactive oxygen species (ROS) and nitric oxide (NO) in differential amounts, within macrophages. Similarly, Rocha-Ramirez et al [120] demonstrated that the pretreatment of macrophages with varying Lactobacillus strains increased their phagocytic and bactericidal activity toward pathogens including S. aureus and E. coli.…”
Section: Discussionmentioning
confidence: 90%
“…[106] Regulating phagocytic macrophage activity by probiotics has been shown to enhance their ability to engulf and kill pathogenic bacteria, thereby augmenting the innate host immune response to infection. [119] However, the mechanisms that impact macrophage phagocytic capacity and downstream phagosomal processing remain poorly understood. The phagocytic response to S. aureus was not investigated in this study and as a dose-dependent response was measured, further investigation is essential to determine the role of LaEP-induced enhanced [B] Cell viability was assessed using a live/ dead assay, where live cells stain green and dead cells, red.…”
Section: Discussionmentioning
confidence: 99%
“…that may activate innate immune cells. Lactobacilli produce a wide array of proteins and metabolites, such as short-chain fatty acids, 40 , 41 that are secreted to the extracellular medium and might exert immunomodulatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…When macrophages were exposed to LGG-conditioned media, their phagocytic and bactericidal activity was increased up to sixfold. This activity was associated with an increment in free radicals production, with the activation of NADPH oxidase, and a slight increase in nitric oxide generation [78].…”
Section: (1) Chemotaxis Is Decreased Due To the High Expression Of 1 ...mentioning
confidence: 93%